Childhood Obesity: Immune Response and Nutritional Approaches - Magrone, Thea; Jirillo, Emilio (Frontiers in Immunology, 2015)
Childhood obesity is characterized by a low grade inflammation status depending on the multicellular release of cytokines, adipokines and reactive oxygen species. In particular, the imbalance between anti-inflammatory T regulatory cells and inflammatory T helper 17 cells seems to sustain such a phlogistic condition. Alterations of gut microbiota since childhood also contribute to the maintenance of inflammation. Therefore, besides preventive measures and caloric restrictions, dietary intake of natural products endowed with anti-oxidant and anti-inflammatory activities may represent a valid interventional approach for preventing and/or attenuating the pathological consequences of obesity. In this regard, the use of prebiotics, probiotics, polyphenols, polyunsaturated fatty acids, vitamins and melatonin in human clinical trials will be described.